ИСПОЛЬЗОВАНИЕ ИНТЕРАКТИВНЫХ МЕТОДОВ ДЛЯ ПОВЫШЕНИЯ КАЧЕСТВА ОБУЧЕНИЯ ДИСЦИПЛИНЕ «ХИМИЯ» В ТЕХНИЧЕСКОМ ВУЗЕ - Худоян, М.В.; Мишенина, И.В.; Темираев, К.Б.; Кокоев, С.З. (SCIENCE and SOCIETY, 2023)
The paper presents an analysis of the organization of the educational process in a technical university based on modern innovative teaching methods. The importance of improving the quality of education, based on a solid basic foundation, is reflected, which is realized in the process of studying the discipline "Physics" in all types of educational activities using such interactive teaching methods.
Keywords: quality of education; interactive teaching methods; individual creative approach to building the educational process; assessment of the quality of education; control over the level of assimilation of knowledge; skills and possessions